Epistemic Injustice and Legitimacy in U.S. Doctoral Education: A Systematic Review of Literature - Farris, Kyle D.; Hansen, Jordan M.; Pasque, Penny A.; 2024; Gonzales, Leslie D. (Review of Educational Research, 2024)
Epistemic injustice is a condition where knowers and knowledge claims are unduly dismissed. Philosophers suggest that epistemic injustice manifests in three forms: testimonial, hermeneutical, and contributory. Although distinct, all forms of epistemic injustice stem from relations of power, privilege, and positionality - where some have the opportunity and authority to legitimize the knowledge contributions of others. The purpose of this study was to explore the presence of epistemic injustice in U.S. doctoral education through a systematic review of literature. We methodically searched hundreds of peer-reviewed journals for studies focused on teaching, advising, peer interaction, doctoral socialization, and other experiences concerning doctoral education across the humanities, social science, and science disciplines. We retained, reviewed, and analyzed 107 manuscripts. Our analysis revealed epistemic injustice in doctoral education as well as rules that foster the conditions for epistemic injustice. Implications for doctoral education and future research are offered.
Keywords: Doctoral Education; Knowledge Production; Learning Environments; Student Knowledge; Higher Education